Improved dynamic parallel imaging coil calibration method robust to respiratory motion with application to first‐pass contrast‐enhanced myocardial perfusion imaging. Issue 6 (7th July 2015) - Fair, Merlin J.; Gatehouse, Peter D.; Drivas, Peter; Firmin, David N.
Abstract : Purpose: To develop an accurate method of performing free‐breathing coil calibration for application to parallel imaging reconstructions of dynamic single‐shot datasets. Methods: Coil calibration data are produced through acquisition of multiple prescans before the accelerated scan, applied during free‐breathing. These multiple free‐breathing prescans (MFPs) provide the necessary coil information for accurate parallel imaging reconstruction of each accelerated frame of a dynamic series, under guidance of an appropriate respiratory position based matching algorithm. This is investigated in myocardial first‐pass perfusion with retrospectively undersampled datasets for analysis with standard calibration techniques to guide prospectively undersampled experiments for specific demonstration of performance against a range of "temporal" calibration techniques. Results: Reconstruction of the retrospectively subsampled datasets with MFP‐calibrated parallel imaging showed significant improvements in relative root‐mean‐square error comparative to all other techniques (all P < 0.05; n = 6) for acceleration factors R > 3. Accelerated acquisitions, reconstructed by means of various temporal calibration techniques and analyzed by visual observer artifact scoring, also demonstrated a large improvement with use of MFPs. Artifact levels were reduced from an average of 2.5 ± 0.6 for the best performing implementation of TGRAPPA to 0.8 ± 0.4 for MFP‐GRAPPA ( P < 0.001; n = 20) (0 = none to 4 = strong, nondiagnostic). Conclusion: MFP as parallel imaging coil calibration data can give improved performance in free‐breathing dynamic MR while maintaining maximal acceleration. Magn Reson Med 75:2315–2323, 2016. © 2015 Wiley Periodicals, Inc.